Improving Spatial Thinking Skills Through Problem-Based Hybrid Learning in Social Science Education for Islamic Students - Sari Dewi; Saiful Amin; Sumarmi Sumarmi; Abdul Bashith; Parida Angriani; Andi Irwan Benardi; Muchammad Akbar Kurniawan (JAMBURA GEO EDUCATION JOURNAL, 2025)
Social science educators in training need strong spatial thinking skills to master geographical concepts, yet evidence shows that undergraduates in Social Science Education often have suboptimal abilities. This study examines the impact of the Problem-Based Hybrid Learning (PBHL) model on spatial reasoning skills of future social science educators. Using a quasi-experimental design, the research compared control and experimental groups through pre-test and post-test evaluations. Participants were Physical Geography students at the Social Sciences Education Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, focusing on Environment and Its Conservation during the 2020/2021 academic year. Purposive sampling selected the experimental class (29 students in class D) receiving PBHL and the control class (29 students in class B) taught with conventional methods. Spatial thinking skills were measured with essay tests of ten items covering comprehension, representation, analysis, spatial interaction, and application. Data were tested for normality and homogeneity, followed by an independent samples t-test. Results showed that PBHL significantly improved students’ spatial thinking skills (p = 0.003 α = 0.05). The experimental group achieved a higher average N-Gain (17.95) than the control group (12.62), with the greatest improvement in representation. The findings indicate that analysis and evaluation stages in PBHL are essential for success. Hybrid platforms provide opportunities for reflection, problem-solving, and information exchange. Future research should expand by testing more variables, replicating the model in other institutions, refining learning tools, enhancing lecturers’ roles as facilitators, and documenting student activities in PBHL implementation.